Multiple Eschars on Lip in Scrub Typhus - Roy, Soumya; Chakrabartty, Subroto; Majumdar, Sumit Datta; Chakravarti, Swati; Barman, Santanu (Journal of Pediatric Infectious Diseases, 2018)
Scrub typhus is an endemic disease of Asian Pacific region, affecting about 1 million people every year. Although it remarkably recovers with doxycycline, the mortality in untreated cases may be as high as 40 to 45%. Owing to the lack of diagnostic facilities for scrub typhus in most places, it is very important to recognize the clinical features. A typical eschar is pathognomonic of the disease. However, this is very rare to be found on the face, and hence can lead to confusions. We present the case of a boy who presented three eschars on the upper lip and was diagnosed as a case of scrub typhus. He responded dramatically with intravenous doxycycline and the eschars healed spontaneously over the next 2 to 3 weeks.
Keywords: scrub typhus; eschar; rickettsia